Humboldt cut - Mick, Allison (EREWHON, an imprint of Kensington Publishing, 2026)
"Jasmine Bay is a nurse for an Oakland mental health facility, battling her own demons, caught in a spiral of suicidal despair. Estranged from her brother James and his wife Tilly, who was once her best friend, Jas has chosen self-isolation to protect herself--even if it means denying herself a hopeful future with co-worker and potential love interest Henry Lewis. When her godmother dies, Jas returns to Redceder for the funeral, a logging town where her grandfather William Whipple made a living deforesting the countryside, ripping and raping apart nature's very foundations for corporate profits. As trees fell to axes and chainsaws, so did dozens of lumberjacks, falling prey to the dangers of their job--and to the ecoterrorism of Jas's grandfather who was lynched for his crime. And buried in the haunted woods are even more dark secrets perpetrated by Jas's family. Unnatural acts giving birth to entities made of human flesh and petrified bark, seeking to avenge the devastation that ravaged their land. It is an inheritance that threatens to consume the remnants of Jas's family, and her very sanity" -- Dust jacket.